GE_GERICHTE A/873/2021 vom 19. August 2021 - GE Cour de justice (2021)
PV d'inventaire; droit de rétention du bailleur; estimation de la valeur des biens inventoriés | LP.283.al1; LP.283.al3; CO.268ss; LP.97.al1; LP.97.al2; LP.276; LP.279.al2